D.E is
"(3y + 2t - 5)dt + (4y+ 3t - 1)dy = 0"Let,
"y=y'+k\\&t=t'+h"Such that
"2h+3k-5=0\\\\3h+4k-1=0"Thus, "(h,k)=(13,-7)" and actual equation reduced to homogeneous equation such that
"\\frac{dy'}{dt'}=-\\dfrac{2t'+3y'}{3t'+4y'}"Let,
"y'=vt'\\implies v+t'\\frac{dv}{dt'}=-\\dfrac{2+3v}{3+4v}\\\\\n\\implies \\frac{dt'}{t'}=-\\dfrac{4v+3}{4v^2+6v+2}dv\\\\\n\\implies \\ln|t'|=-\\frac{1}{2}\\ln|(2v^2+3v+1)|\\\\\n\\implies c t'^2=\\frac{1}{2v^2+3v+1}\\\\\n\\implies ct'^4=\\frac{1}{2y'^2+3y't'+t'^2}"But,
"y'=y+7\\&t'=t-13"Thus,
"c(t-13)^4=\\frac{1}{2(y+7)^2+3(y+7)(t-13)+(t-13)^2}"As, "y(-1)=2" ,thus
"c=\\frac{1}{14^4(-20)}"Then the solution will be
"-\\frac{1}{20\\cdot14^4}=\\frac{1}{2(y+7)^2+3(y+7)(t-13)+(t-13)^2}"
Comments
Leave a comment